Soluble Interleukin-15 Complexes Are Generated In Vivo by Type I Interferon Dependent and Independent Pathways - Anthony, Scott M. (PLoS One, 2015)
Interleukin (IL)-15 associates with IL-15Rα on the cell surface where it can be cleaved into soluble cytokine/receptor complexes that have the potential to stimulate CD8 T cells and NK cells. Unfortunately, little is known about the in vivo production of soluble IL-15Rα/IL-15 complexes (sIL-15 complexes), particularly regarding the circumstances that induce them and the mechanisms responsible. The main objective of this study was to elucidate the signals leading to the generation of sIL-15 complexes. In this study, we show that sIL-15 complexes are increased in the serum of mice in response to Interferon (IFN)-α. In bone marrow derived dendritic cells (BMDC), IFN-α increased the activity of ADAM17, a metalloproteinase implicated in cleaving IL-15 complexes from the cell surface. Moreover, knocking out ADAM17 in BMDCs prevented the ability of IFN-α to induce sIL-15 complexes demonstrating ADAM17 as a critical protease mediating cleavage of IL-15 complexes in response to type I IFNs. Type I IFN signaling was required for generating sIL-15 complexes as in vivo induction of sIL-15 complexes by Poly I:C stimulation or total body irradiation (TBI) was impaired in IFNAR-/- mice. Interestingly, serum sIL-15 complexes were also induced in mice infected with Vesicular stomatitis virus (VSV) or mice treated with agonistic CD40 antibodies; however, sIL-15 complexes were still induced in IFNAR-/- mice after VSV infection or CD40 stimulation indicating pathways other than type I IFNs induce sIL-15 complexes. Overall, this study has shown that type I IFNs, VSV infection, and CD40 stimulation induce sIL-15 complexes suggesting the generation of sIL-15 complexes is a common event associated with immune activation. These findings reveal an unrealized mechanism for enhanced immune responses occurring during infection, vaccination, inflammation, and autoimmunity.